Cognitive bias modification training in adolescents: effects on interpretation biases and mood. - Lothmann, C; Holmes, E; Chan, S; Lau, J (2011)
BACKGROUND: Negative biases in the interpretation of ambiguous material have been linked to anxiety and mood problems. Accumulating data from adults show that positive and negative interpretation styles can be induced through cognitive bias modification (CBM) paradigms with accompanying changes in mood. Despite the therapeutic potential of positive training effects, training paradigms have not yet been explored in adolescents. METHODS: Eighty-two healthy adolescents (aged 13-17 years) were randomly allocated to either positive or negative CBM training. To assess training effects on interpretation bias, participants read ambiguous situations followed by test sentences with positive or negative interpretations of the situation. Participants rated the similarity of these sentences to the previously viewed ambiguous situations. Training effects on negative and positive affect were assessed using visual analogue scales before and after training. RESULTS: After training, adolescents in the negative condition drew more negative and fewer positive interpretations of new ambiguous situations than adolescents in the positive condition. Within the positive condition, adolescents endorsed more positive than negative interpretations. In terms of mood changes, positive training resulted in a significant decrease in negative affect across participants, while the negative condition led to a significant decrease in positive affect among male participants only. CONCLUSION: This is the first study to demonstrate the plasticity of interpretation bias in adolescents. The immediate training effects on mood suggest that it may be possible to train a more positive interpretation style in youth, potentially helping to protect against anxiety and depressive symptoms.